ENDOGENOUS ANTIOXIDANT COMPLEX AND SUPEROXIDE DISMUTASE PERFORMED IN SOME NON-AIRBREATHING FISHES - SINGH, SHIVENDRA KUMAR; BHAT, RAYEES AHMAD (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
The toxic effect could be evaluated through the assay of antioxidant enzymes. Such enzymes safeguard life forms against oxidative damage by toxic metals. Oxidative stress has been a significant feature of toxicology in recent times and also has gained growing recognition. Analysis has developed from the simple study of the symptoms of oxidative damage only at stage of the organism to the explanation of the fundamental processes at the biochemical and metabolic stages. There is the confirmation that oxidative stress often has an ecological significance, especially in the aquatic ecosystem, which is really the ultimate trap for several oxidative stress-producing contaminants. Based on the evidence presented with both mammalian and swimming pool environments, the detrimental and adaptive pathways of oxidative stress tend to be somewhat identical. The current study also points out is that fish can serve as significant bio - indicators and therefore can act as a viable substitute. In the present study a survey of levels of the antioxidant defence enzyme, superoxide dismutase were conducted in a varieties of water non Air breathing fishes collected from different sites using various metabolically active tissues (viz. liver, brain, kidney, gills, heart etc.) of the investigated fishes. The results showed that the highest Cu-Zn SOD (9.3 unites. mg-1 protein) was found in liver and lowest Cu-Zn SOD (0.1 units. mg-1 protein) was observed in the brain tissue of the fish Labeo rohita compared with other ones.